Creating digital collections : a practical guide - Zhang, Allison B. (Chandos information professional series., 2008)
Libraries recognize the importance of digitizing archival material to improve access to and preservation of their special collections. This book provides a step-by-step guide for creating digital collections, including examples and practical tips that have never been published before.